An MTH1-targeted nanosystem for enhanced PDT via improving cellular sensitivity to reactive oxygen species. Issue 34 (11th April 2018) - Fan, Huanhuan; Zhang, Lili; Hu, Xiaoxiao; Zhao, Zilong; Bai, Huarong; Fu, Xiaoyi; Yan, Guobei; Liang, Li-Hui; Zhang, Xiao-Bing; Tan, Weihong
Abstract : An MTH1-targeted nanosystem is developed for enhanced PDT through inhibiting MTH1 protein and improving cellular sensitivity to reactive oxygen species. Abstract : Herein, we developed a strategy to attack the cancer cell defense system against reactive oxygen species to improve photodynamic therapy efficacy with a Ce6@MSN@MTH1 siRNA nanosystem, which was demonstrated to improve cellular sensitivity to reactive oxygen species through suppressing MTH1 protein in cancer cells.